Sheet titanium alloy wear-resistant hydrogen permeation layer and preparation method thereof

The preparation of hydrogen permeability layer on the surface of titanium alloy through spontaneous hydrogen permeability technology solves the problem of poor wear resistance of titanium alloy, and achieves significant improvement in surface hardness and wear resistance, which is suitable for low-cost mass production of small-sized titanium alloy structural parts.

CN119736575AActive Publication Date: 2025-04-01XIAN UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411901249.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Titanium and titanium alloys have large friction coefficient, easy adhesion and poor wear resistance, which leads to premature wear of the device, limiting their application range in the preparation of new titanium alloy devices.

Method used

A hydrogen permeation layer was prepared on the surface of the titanium alloy by using spontaneous hydrogen permeation technology. By electrolyzing the titanium alloy as the cathode and the metal with a lower electric potential as the anode, the current, temperature and time were controlled to prepare a hydrogen permeation layer with a hydrogen content of 0.001%-0.018%.

Benefits of technology

The surface hardness and wear resistance of titanium alloy are significantly improved, forming hydrogen permeability strengthening alloy, avoiding hydride precipitation and reduced toughness, and achieving low-cost mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736575A_ABST
    Figure CN119736575A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a sheet titanium alloy wear-resistant hydrogen permeation layer, which comprises the following steps: step 1, cathode and anode surface treatment: grinding the surfaces of a titanium alloy and another metal with potential lower than that of the titanium alloy, and then polishing; step 2, putting the NaCl solution into a hydrogen production container, wherein materials used in the hydrogen production container are prevented from chemically reacting with hydrogen atoms; 3, spontaneous hydrogen permeation is conducted to prepare a hydrogen permeation layer, metal with the potential lower than that of the titanium alloy serves as an anode, the titanium alloy serves as a cathode, the cathode and the anode are connected through a wire, the cathode and the anode are placed in a NaCl solution, the current is controlled to range from 5 mA to 100 mA, the hydrogen permeation temperature ranges from 25 DEG C to 100 DEG C, the hydrogen permeation time ranges from 10 h to 60 h, and the hydrogen permeation layer is prepared on the surface of the titanium alloy; the hydrogen permeation layer can improve the hardness of the titanium alloy and improve the wear resistance of the titanium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface modification, and in particular relates to a wear-resistant hydrogen permeation layer of a thin plate titanium alloy and a preparation method thereof. Background Art

[0002] Titanium and titanium alloys are widely used in petrochemical, tableware, packaging and other fields due to their high specific strength and good biocompatibility. However, titanium and titanium alloys have a large friction coefficient, are easy to adhere, and have poor wear resistance, which may cause premature wear of titanium alloy devices, reduce their service life, and limit their application in the preparation of new titanium alloy devices.

[0003] Hydrogen infiltration changes the microstructure of titanium alloy phases, resulting in an increase in lattice parameters and the generation of micro-internal stress. If the increase in hydrogen content does not exceed the threshold, the room temperature hardness, strength and other properties of the alloy surface will be significantly improved. Although hydrogenation technology represented by hot hydrogenation can improve the high temperature formability of titanium alloys, few studies have focused on improving the surface hardness of room temperature hydrogenated alloys. This is because the vacuum hot hydrogenation temperature is high, which often improves the initial microstructure of the alloy, which is not conducive to improving mechanical properties. Spontaneous electrolytic hydrogenation is carried out at low temperatures (<100°C), and the hydrogenation content can be controlled by regulating the hydrogenation time. Moreover, the TiNi in the alloy x The high surface energy of the precipitates hinders the accumulation of hydrogen adsorption and prevents the alloy toughness from being significantly reduced, thereby greatly improving the wear resistance of the alloy surface. It is suitable for surface hydrogenation hardening treatment of small-sized titanium alloy structural parts, and can realize low-cost mass production of surface hardened titanium alloy products. Summary of the invention

[0004] The purpose of the present invention is to provide a wear-resistant hydrogen permeation layer of a thin plate titanium alloy and a preparation method thereof. The hydrogen permeation layer can improve the surface hardness and wear resistance of the TiNi alloy.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a wear-resistant hydrogen permeation layer of a thin titanium alloy plate, specifically comprising the following steps:

[0007] Step 1, cathode and anode surface treatment, grinding the surface of the titanium alloy and another metal with a lower potential than the titanium alloy, and then polishing;

[0008] Step 2, placing the NaCl solution into a hydrogen production container, wherein the material used in the hydrogen production container avoids chemical reaction with hydrogen atoms;

[0009] Step 3, spontaneous hydrogenation to prepare a hydrogen permeation layer, using a metal with a lower potential than the titanium alloy as an anode and the titanium alloy as a cathode, connecting the cathode and the anode with a wire, and placing the cathode and the anode in a NaCl solution, the current size is controlled at 5-100mA, the hydrogen permeation temperature is 25-100°C, the hydrogen permeation time is 10h-60h, and a hydrogen permeation layer is prepared on the surface of the titanium alloy.

[0010] Furthermore, the specific method of step 1 is: the surfaces of the titanium alloy and another metal with a lower electric potential than the titanium alloy are polished with 500, 1000, 1200, and 2000 sandpapers in sequence, and then polished with a silicon dioxide aqueous solution.

[0011] Furthermore, in step 1, the titanium alloy is a titanium-nickel alloy, and the stable potential of the titanium-nickel alloy in NaCl solution is +0.09V.

[0012] Furthermore, in step 1, another metal with a lower potential than the titanium alloy is zinc, and its potential is -0.76V.

[0013] Furthermore, the hydrogen production container in step 2 is a polyurethane square container.

[0014] Furthermore, in step 2, the concentration of the NaCl solution is 4.6%.

[0015] Furthermore, in step 3, the wires are connected to the cathode and the anode by soldering, and the connection joints are not immersed in the NaCl solution.

[0016] Furthermore, in step 3, by adjusting the hydrogenation temperature and hydrogenation time, the hydrogen content in the prepared hydrogenation layer is 0.001%-0.018%.

[0017] The hydrogen permeation layer prepared according to the above-mentioned method for preparing a wear-resistant hydrogen permeation layer of a thin plate titanium alloy is characterized in that the matrix phase with lattice distortion and high hardness TiNi X The composition of the precipitated phase: the hydrogen atoms in the hydrogen permeation layer come from the hydrogen in the electrolyzed water.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The wear-resistant hydrogen permeation layer of the titanium alloy sheet prepared by the invention can form a hydrogen-permeated strengthened alloy, thereby effectively improving the surface strength and wear resistance of the alloy.

[0020] The wear-resistant hydrogen permeation layer of the titanium alloy thin plate prepared by the present invention has a precipitated phase in the alloy that effectively regulates the uniform distribution of hydrogen in the alloy, has no hydride precipitation, and has no obvious reduction in toughness.

[0021] The wear-resistant hydrogen permeation layer of the titanium alloy thin plate prepared by the invention adopts potential difference as the hydrogen permeation power source to reduce the hydrogen permeation rate, and the hydrogen permeation amount can be quantitatively controlled.

[0022] The wear-resistant hydrogen permeation layer of the titanium alloy thin plate prepared by the present invention adopts a low hydrogen content to prepare the hydrogenated layer, does not need subsequent vacuum annealing to adjust the hydrogen content, has low cost and is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 An XRD diagram of lattice distortion of a wear-resistant hydrogen permeation layer of a thin plate titanium alloy prepared in Example 1-5 of the present invention;

[0024] Figure 2 This is a distribution diagram of the titanium alloy precipitation phase in the wear-resistant hydrogen permeation layer of a thin plate titanium alloy prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0025] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0026] The invention provides a wear-resistant hydrogen permeation layer of a thin plate titanium alloy, which consists of a matrix phase with lattice distortion and a high-hardness precipitation phase. The hydrogen atoms in the hydrogen permeation layer come from hydrogen in electrolyzed water.

[0027] The hydrogen permeation in the electrolyzed water is to use the titanium alloy with high potential as the cathode and other metals with low potential as the anode, and connect the two metals with a wire and place them in a NaCl conductive solution; the current is controlled at 5-100mA, the hydrogen permeation temperature is 35-100℃, and the hydrogen permeation time is 10h-60h

[0028] The reasons for using the potential difference between two metals as the driving force for electrolysis of water are as follows:

[0029] 1. The potential difference between titanium-nickel alloy and zinc is 0.67V. The amount and rate of hydrogen absorption by titanium-nickel alloy can be controlled by adjusting the hydrogen permeation temperature and time. The workpiece is not restricted by shape.

[0030] 2. Titanium-nickel alloy still has high strength and toughness when the hydrogen absorption is 0.018%, and a large amount of TiNi in the alloy X The precipitated phase helps to evenly distribute hydrogen atoms and avoid the formation of brittle hydrides.

[0031] 3. The hydrogen content of the prepared alloy hydrogenation layer is regulated between 0.001% and 0.018%, and the hardness of the alloy is increased by lattice distortion of the matrix phase.

[0032] The present invention also provides a method for preparing a wear-resistant hydrogen permeation layer of a thin plate titanium alloy, and the specific steps are as follows:

[0033] A method for preparing a wear-resistant hydrogen permeation layer of a thin titanium alloy plate, specifically comprising the following steps:

[0034] Step 1, cathode and anode surface treatment, the surfaces of the titanium-nickel alloy and another metal with a lower potential than the titanium-nickel alloy are polished with 500, 1000, 1200, and 2000 sandpapers in sequence, and then polished with a silicon dioxide aqueous solution. The stable potential of the titanium-nickel alloy in the NaCl solution is +0.09V, and the potential of zinc is -0.76V;

[0035] Step 2, placing a NaCl solution into a hydrogen production container, wherein the concentration of the NaCl solution is 4.6%, and the hydrogen production container is a polyurethane square container, and the material used in the hydrogen production container avoids chemical reaction with hydrogen atoms;

[0036] Step 3, spontaneous hydrogenation to prepare a hydrogen permeation layer, using a metal with a lower potential than the titanium alloy as an anode and the titanium alloy as a cathode, connecting the cathode and the anode with a wire, and placing the cathode and the anode in a NaCl solution, connecting the wire to the cathode and the anode with solder, and the connecting joint part is not immersed in the NaCl solution, the current size is controlled at 5-100mA, the hydrogen permeation temperature is 25-100°C, the hydrogen permeation time is 10h-60h, and a hydrogen permeation layer is prepared on the surface of the titanium alloy. By adjusting the hydrogen permeation temperature and the hydrogen permeation time, the hydrogen content in the prepared hydrogen permeation layer is 0.001%-0.018%.

[0037] The hydrogen-permeated alloy prepared in step 3 was placed in silicone oil in a glass tube and stored at room temperature in preparation for subsequent wear resistance experiments.

[0038] Example 1

[0039] Step 1, cathode and anode surface treatment: the surfaces of the titanium-nickel alloy and zinc are polished with 500, 1000, 1200, 2000 sandpaper in sequence, and then polished with a silicon dioxide aqueous solution.

[0040] Step 2, preparation of hydrogen production container: put NaCl solution into the hydrogen production container, the concentration of NaCl solution is 4.6%, the hydrogen production container adopts polyurethane square container, the material used avoids chemical reaction with hydrogen ions, and electrons can flow freely in the container solution.

[0041] Step 3: Spontaneous hydrogenation to prepare a hydrogen permeation layer: zinc is used as the anode and titanium-nickel alloy is used as the cathode. The cathode and the anode are connected with a wire, and the cathode and the anode are placed in a NaCl solution. The wire is connected to the cathode and the anode with solder, and the connection joint is not immersed in the NaCl solution. The current is controlled at 5 mA, the hydrogen permeation temperature is 27°C, and the hydrogen permeation time is 10 hours. A hydrogen permeation layer is prepared on the surface of the titanium alloy.

[0042] The hydrogen-permeated alloy prepared in step 3 was placed in silicone oil in a glass tube and stored at room temperature in preparation for subsequent wear resistance experiments.

[0043] The wear-resistant hydrogen permeated layer of the titanium alloy thin plate prepared in this embodiment has a surface hydrogen content of 0.0012% after a hydrogen content test experiment. The nano hardness of the surface hydrogen permeated layer is 6.32Gpa, the wear amount is 3.2mg, and the friction coefficient is 0.85 after a hardness tester test, which has good wear resistance.

[0044] Example 2

[0045] Step 1, cathode and anode surface treatment: the surfaces of the titanium-nickel alloy and zinc are polished with 500, 1000, 1200, 2000 sandpaper in sequence, and then polished with a silicon dioxide aqueous solution.

[0046] Step 2, preparation of hydrogen production container: put NaCl solution into the hydrogen production container, the concentration of NaCl solution is 4.6%, the hydrogen production container adopts polyurethane square container, the material used avoids chemical reaction with hydrogen ions, and electrons can flow freely in the container solution.

[0047] Step 3: Spontaneous hydrogenation to prepare a hydrogen permeation layer: zinc is used as the anode and titanium-nickel alloy is used as the cathode. The cathode and the anode are connected with a wire, and the cathode and the anode are placed in a NaCl solution. The wires are connected to the cathode and the anode with solder, and the connection joints are not immersed in the NaCl solution. The current is controlled at 10 mA, the hydrogen permeation temperature is 25°C, and the hydrogen permeation time is 60 hours.

[0048] The hydrogen-permeated alloy prepared in step 3 was placed in silicone oil in a glass tube and stored at room temperature in preparation for subsequent wear resistance experiments.

[0049] The wear-resistant hydrogen permeated layer of the titanium alloy sheet prepared in this embodiment has a surface hydrogen content of 0.0051%. After testing with a hardness tester, the nano-hardness of the surface hydrogen permeated layer is 7.21 Gpa, the wear amount is 3.03 mg, and the friction coefficient is 0.81, which has good wear resistance.

[0050] Example 3

[0051] Step 1, cathode and anode surface treatment: the surfaces of the titanium-nickel alloy and zinc are polished with 500, 1000, 1200, 2000 sandpaper in sequence, and then polished with a silicon dioxide aqueous solution.

[0052] Step 2, preparation of hydrogen production container: put NaCl solution into the hydrogen production container, the concentration of NaCl solution is 4.6%, the hydrogen production container adopts polyurethane square container, the material used avoids chemical reaction with hydrogen ions, and electrons can flow freely in the container solution.

[0053] Step 3: Spontaneous hydrogenation to prepare a hydrogen permeation layer: zinc is used as the anode and titanium-nickel alloy is used as the cathode. The cathode and the anode are connected with a wire, and the cathode and the anode are placed in a NaCl solution. The wires are connected to the cathode and the anode with solder, and the connection joints are not immersed in the NaCl solution. The current is controlled at 20 mA, the hydrogen permeation temperature is 27°C, and the hydrogen permeation time is 20 hours.

[0054] The hydrogen-permeated alloy prepared in step 3 was placed in silicone oil in a glass tube and stored at room temperature in preparation for subsequent wear resistance experiments.

[0055] The wear-resistant hydrogen permeated layer of the titanium alloy sheet prepared in this embodiment has a surface hydrogen content of 0.0102%. After being tested by a hardness tester, the nano-hardness of the surface hydrogen permeated layer is 7.08 Gpa, the wear amount is 2.98 mg, and the friction coefficient is 0.76, which has good wear resistance.

[0056] Figure 2 The distribution diagram of the titanium alloy precipitation phase in the wear-resistant hydrogen permeation layer of a thin titanium alloy prepared in this embodiment 3 is as follows: Figure 2 It can be seen that the precipitated phase is evenly distributed in the titanium-nickel alloy matrix, and the quantitative interface promotes the uniform distribution of hydrogen atoms.

[0057] Example 4

[0058] Step 1, cathode and anode surface treatment: the surfaces of the titanium-nickel alloy and zinc are polished with 500, 1000, 1200, 2000 sandpaper in sequence, and then polished with a silicon dioxide aqueous solution.

[0059] Step 2, preparation of hydrogen production container: put NaCl solution into the hydrogen production container, the concentration of NaCl solution is 4.6%, the hydrogen production container adopts polyurethane square container, the material used avoids chemical reaction with hydrogen ions, and electrons can flow freely in the container solution.

[0060] Step 3: Spontaneous hydrogenation to prepare a hydrogen permeation layer: zinc is used as the anode and titanium-nickel alloy is used as the cathode. The cathode and the anode are connected with a wire, and the cathode and the anode are placed in a NaCl solution. The wires are connected to the cathode and the anode with solder, and the connection joints are not immersed in the NaCl solution. The current is controlled at 100 mA, the hydrogen permeation temperature is 50°C, and the hydrogen permeation time is 20 hours.

[0061] The hydrogen-permeated alloy prepared in step 3 was placed in silicone oil in a glass tube and stored at room temperature in preparation for subsequent wear resistance experiments.

[0062] The wear-resistant hydrogen permeated layer of the titanium alloy sheet prepared in this embodiment has a surface hydrogen content of 0.0125%. After being tested by a hardness tester, the nano-hardness of the surface hydrogen permeated layer is 7.11 Gpa, the wear amount is 3.01 mg, and the friction coefficient is 0.78, which has good wear resistance.

[0063] Example 5

[0064] Step 1, cathode and anode surface treatment: the surfaces of the titanium-nickel alloy and zinc are polished with 500, 1000, 1200, 2000 sandpaper in sequence, and then polished with a silicon dioxide aqueous solution.

[0065] Step 2, preparation of hydrogen production container: put NaCl solution into the hydrogen production container, the concentration of NaCl solution is 4.6%, the hydrogen production container adopts polyurethane square container, the material used avoids chemical reaction with hydrogen ions, and electrons can flow freely in the container solution.

[0066] Step 3: Spontaneous hydrogenation to prepare a hydrogen permeation layer: zinc is used as the anode and titanium-nickel alloy is used as the cathode. The cathode and the anode are connected with a wire, and the cathode and the anode are placed in a NaCl solution. The wires are connected to the cathode and the anode with solder, and the connection joints are not immersed in the NaCl solution. The current is controlled at 20 mA, the hydrogen permeation temperature is 100°C, and the hydrogen permeation time is 20 hours.

[0067] Step 4: Place the hydrogen-impregnated alloy prepared in step 3 in silicone oil in a glass tube and store it at room temperature in preparation for subsequent wear resistance experiments.

[0068] The wear-resistant hydrogen permeated layer of the titanium alloy sheet prepared in this embodiment has a surface hydrogen content of 0.0176%. After testing with a hardness tester, the nano-hardness of the surface hydrogen permeated layer is 6.5 Gpa, the wear amount is 3.02 mg, and the friction coefficient is 0.82, which has good wear resistance.

[0069] The XRD diagram of the lattice distortion of the wear-resistant hydrogen permeation layer of a thin plate titanium alloy prepared in Examples 1-5 of the present invention is as follows: Figure 1 As shown in Figure 2, as the hydrogen content increases, the 2θ angle of the matrix phase peak moves to the left, and the lattice parameter changes from Increase to The lattice distortion volume increased by 0.7%.

[0070] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A method for preparing a wear-resistant hydrogen permeation layer of a thin plate titanium alloy, characterized in that: The specific steps include: Step 1, cathode and anode surface treatment, grinding the surface of the titanium alloy and another metal with a lower potential than the titanium alloy, and then polishing; Step 2, placing the NaCl solution into a hydrogen production container, wherein the material used in the hydrogen production container avoids chemical reaction with hydrogen atoms; Step 3, spontaneous hydrogenation to prepare a hydrogen permeation layer, using a metal with a lower potential than the titanium alloy as an anode and the titanium alloy as a cathode, connecting the cathode and the anode with a wire, and placing the cathode and the anode in a NaCl solution, the current size is controlled at 5-100mA, the hydrogen permeation temperature is 25-100°C, the hydrogen permeation time is 10h-60h, and a hydrogen permeation layer is prepared on the surface of the titanium alloy.

2. The method for preparing a wear-resistant hydrogen permeation layer of a thin plate titanium alloy according to claim 1, characterized in that: The specific method of step 1 is: the surfaces of the titanium alloy and another metal with a lower electric potential than the titanium alloy are polished with 500, 1000, 1200, and 2000 sandpapers in sequence, and then polished with a silicon dioxide aqueous solution.

3. A method for preparing a wear-resistant hydrogen permeation layer of a titanium alloy thin plate according to any one of claims 1 or 2, characterized in that: The titanium alloy in step 1 is a titanium-nickel alloy, and the stable potential of the titanium-nickel alloy in NaCl solution is +0.09V.

4. A method for preparing a wear-resistant hydrogen permeation layer of a titanium alloy thin plate according to any one of claims 1 or 2, characterized in that: In step 1, another metal with a lower potential than the titanium alloy is zinc, which has a potential of -0.76V.

5. The method for preparing a wear-resistant hydrogen permeation layer of a thin plate titanium alloy according to claim 1, characterized in that: In step 2, the hydrogen production container adopts a polyurethane square container.

6. The method for preparing a wear-resistant hydrogen permeation layer of a titanium alloy thin plate according to claim 1, characterized in that: The concentration of NaCl solution in step 2 is 4.6%.

7. The method for preparing a wear-resistant hydrogen permeation layer of a titanium alloy thin plate according to claim 1, characterized in that: In step 3, the wires are connected to the cathode and the anode by soldering, and the connection joints are not immersed in the NaCl solution.

8. The method for preparing a wear-resistant hydrogen permeation layer of a titanium alloy thin plate according to claim 1, characterized in that: In step 3, by adjusting the hydrogenation temperature and hydrogenation time, the hydrogen content in the prepared hydrogenation layer is 0.001%-0.018%.

9. The hydrogen permeable layer prepared by the method for preparing a wear-resistant hydrogen permeable layer of a thin plate titanium alloy according to any one of claims 1 to 8 is characterized in that: The matrix phase with lattice distortion and high hardness TiNi X The composition of the precipitated phase: the hydrogen atoms in the hydrogen permeation layer come from the hydrogen in the electrolyzed water.

Citation Information

Patent Citations

  • Application of surface hydrogen permeation titanium alloy in oxalic acid solution

    CN110241377A

  • Electrochemical cathode hydrogen charging method for metal and alloy samples

    CN110530690A

  • Electrochemical plant treatment device and method

    CN116234433A

  • Hydrogen separation device for graded recovery of H2 / CO2 / small amount of CO mixed gas

    CN118142312A

  • Circulating thermal hydrogen preparation method with refined titanium alloy grains

    CN118326297A